Forum on Science, Technology and Innovation for Sustainable Development, ICSU, Rio +20 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The Forum on Science, Technology and Innovation for Sustainable Development was a major five-day event in the days just prior to the Rio+20 conference in Rio de Janeiro. Organised by the International Council for Science (ICSU), in partnership with UNESCO, the World Federation of Engineering Organizations (WFEO), the International Social Science Council (ISSC), the Brazilian Ministry of Science, Technology and Innovation and the Brazilian Academy of Sciences, the Forum aimed to provide a platform for the science, technology and innovation (STI) community to highlight key messages within the Rio+20 context, and to enter into dialogue with policy-makers and other stakeholders.